Assistancing and Recogning to the Students on English for Business in Bireuen, Aceh District - Misnawati, Zuraini (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
Bireuen is one of the district which make a village for Acheness cakes home industry production. A various cakes in Acheness have a quality. English for business is one the English subject must be taken by the students. English for Business is the activities of making, buying and buying selling in good service and then exchanging them for the money, the activities can be completed at home. Some problems were faced by the people; such as is not good in packaging, is not interesting cointainer, and do not how to promote their product by using social media to increase their income and also improve their quality of the products in Bireuen district, Acheh province. The method of this study is help the people by giving the suggestion and providing packing product in interesting cointainer. Giving the deeply understanding to the students and also the people in developing the mindset of enterpreneurship, the facillitate in equipment, marketing strategy, and marketing management. The results of this program are improve the students in comprehending the English for business, a good packaging and interesting cointaners, increasing the income for the people through promote in media social.